2018
DOI: 10.1159/000486537
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Stenting for Treatment of Symptomatic Carotid Webs: A Single-Center Case Series

Abstract: Background and Purpose: Carotid webs are an increasingly recognized cause of acute is­chemic stroke, particularly in younger adults. The optimal medical and surgical strategies for managing these lesions have not been well established. We report a single-center case series of carotid stenting for treatment of symptomatic carotid webs. Materials and Methods: Consecutive patients undergoing stent placement for treatment of symptomatic carotid webs were included. Carotid webs were defined as a thin intraluminal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Surgery has been proposed as invasive treatment option, 3 and small series of carotid endarterectomy in symptomatic CaW have reported data for acceptable safety and efficacy after a median follow-up around 12 months. 3,13,[24][25][26] Endovascular procedure has also been reported as safe, 27 and a recent study 28 showed that the procedure performed in 24 symptomatic CaW patients was effective to prevent recurrence after a median clinical follow-up of 12 months. Although no randomized data are available, invasive treatment such as surgery or stenting seems now increasingly proposed as secondary preventive strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery has been proposed as invasive treatment option, 3 and small series of carotid endarterectomy in symptomatic CaW have reported data for acceptable safety and efficacy after a median follow-up around 12 months. 3,13,[24][25][26] Endovascular procedure has also been reported as safe, 27 and a recent study 28 showed that the procedure performed in 24 symptomatic CaW patients was effective to prevent recurrence after a median clinical follow-up of 12 months. Although no randomized data are available, invasive treatment such as surgery or stenting seems now increasingly proposed as secondary preventive strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical endarterectomy for a carotid web has a success rate similar to stenting, but with greater cost, longer recovery time, and more risk of neck hematoma or anesthetic complication than endovascular procedures. 6,2527 Joux et al. in a 5 year study on Afro-Caribbean patients identified 25 patients with embolic stroke associated with a carotid web.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid artery stenting is a safe and effective method for treating a carotid web, with low perioperative complications and good short-term results. The time of carotid artery stent placement is shorter than that of carotid endarterectomy [ 15 ]. The present study had a small sample size.…”
Section: Treatment Of a Carotid Webmentioning
confidence: 99%